Near infrared dye-encapsulated polymeric nanoparticles with enhanced photostability under hyperthermal condition - Soeriawidjaja, Banyu Firdaus; Kang, Mingyeong; Kim, Hanseong; Yang, Hyun Kyoung; Kim, Jong H.; Kwak, Minseok (Molecular Crystals and Liquid Crystals, 2019)
Polymeric micelles are versatile nanocarriers to carry hydrophobic moieties within the core in aqueous media. We report engineered polymeric micelles encapsulating highly photostable organic near-infrared (NIR) dye, IR788, for generating heat under NIR irradiation. In addition, the core of micelle is stabilized via semi-interpenetrating network formation (sIPN), which ensures stable loading under low temperature and enhances biocompatibility in cell experiment.
Keywords: Hydrophobic moieties; Low temperatures; Near infra red; Near-infrared dyes; Photo-stability; Polymeric micelle; Polymeric nanoparticles; Semi-interpenetrating networks